Study of electron acceleration and X-ray radiation as a function of plasma density in capillary-guided laser wakefield accelerators - Ju, L.; Svensson, K.; Ferrari, Hugo Emilio; Döpp, A.; Cassou, K.; Genoud, G.; Wojda, F.; Burza, M.; Persson, A.; Lundh, O.; Wahlström, C. G.; Cros, B. (American Institute Of Physics, 2013)
Fil: Ju, L.. Universite de Paris Xi; Francia;